(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Retardation of environmental quality is the result of industrialization and various other activities. Population explosion, urbanization, various agriculture chemicals and pesticides, increasing temperature etc. are responsible for environmental degradation.Chief environmental factors are cutting of trees and forest, extra use of various chemicals in agriculture, excessive use of plastics and urbanization. Every cause plays an important role in retardation and degradation of quality of environment.